Ceiling beam in the sanctum, Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
The ceiling beam in the sanctum depicts an array of warriors marching towards the right on its side, while the lower face of the beam is richly carved with vegetation foliage.